2022
DOI: 10.21608/svuijas.2022.95417.1141
|View full text |Cite
|
Sign up to set email alerts
|

Mulching strategy provides higher healthier, and cleaner tomato (Solanum lycopersicum) crop in a profitable way

Abstract: To manage natural resources and achieve agricultural sustainability, effective production strategies are required. For a healthier crop and a cleaner environment, reducing or eliminating chemical use is also a desirable goal. The goal of this study was to see how soil polyethylene mulch affected tomato crop output and quality. The Experimental Farm of the Faculty of Agriculture, Sohag University, Egypt, was used for two consecutive early summer seasons production. Manual weeding was used as a positive control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…straw or wood chips), polyethylene foils, polypropylene nonwoven fabrics, gravels, biodegradable plastic foils are used to serve these purposes [25,26]. Plastic mulching plays an important role in crop growth and development as it conserves soil moisture and decreases weed infestation [27][28][29]. Furthermore, plastic mulching adjusts soil temperature, improves crop yield, and decreases costs incurred on herbicides and fertilizers [30].…”
Section: Introductionmentioning
confidence: 99%
“…straw or wood chips), polyethylene foils, polypropylene nonwoven fabrics, gravels, biodegradable plastic foils are used to serve these purposes [25,26]. Plastic mulching plays an important role in crop growth and development as it conserves soil moisture and decreases weed infestation [27][28][29]. Furthermore, plastic mulching adjusts soil temperature, improves crop yield, and decreases costs incurred on herbicides and fertilizers [30].…”
Section: Introductionmentioning
confidence: 99%
“…In mulching Significantly higher height was found in 30 DAT (56.91 cm), 45 DAT (92.50 cm), 60 DAT (141.35 cm), and 75 DAT (173.6 cm). Hamed et al (2022) revealed that plastic mulching increases vegetative growth and maximizes plant height. There were several reports which showed the plastic mulching had increased soil temperature and early shoot growth in tomato (Qasem, 2019).…”
Section: Effect Of Mulching and Nitrogen Dose On Height Of Tomatomentioning
confidence: 99%